Long-Term l-Serine Administration Reduces Food Intake and Improves Oxidative Stress and Sirt1/NFκB Signaling in the Hypothalamus of Aging Mice - Zhou, Xihong; Zhang, Haiwen; He, Liuqin; Wu, Xin; Yin, Yulong (Frontiers in Endocrinology, 2018)
Serine has recently been shown to reduce oxidative stress and inflammation, which, when occurring in the hypothalamus, contribute to age-related obesity. To explore whether long-term serine administration reduces oxidative stress and body weight in aging mice, different concentrations of L-serine dissolved in water were administered to 18-month-old C57BL/6J mice, for six months. Results show that administration of 0.5% (w/v) L-serine significantly reduced food intake and body weight gain during the experiment. Moreover, administration of 0.5% L-serine decreased the concentrations of leptin, malondialdehyde, interleukin (IL)-1β, and IL-6, while increasing concentrations of superoxide dismutase and glutathione, in both the serum and hypothalamus. Reactive oxygen species and the activity of nicotinamide adenine dinucleotide phosphate oxidase were reduced in the hypothalamus of aging mice administered with L-serine. In addition, the expression of the leptin receptor was increased, while the levels of neuropeptide Y and agouti-related protein were decreased in mice that had been administered with 0.5% L-serine. Expressions of Sirt1 and of phosphorylated STAT 3 (pSTAT3) were increased, while phosphorylated NFκB was decreased. These results indicate that long-term L-serine administration reduces body weight by decreasing orexigenic peptide expression and reduces oxidative stress and inflammation during aging in mice and suggest that serine may exert these effects by modulating the Sirt1/NFκB pathway. Thus, L-serine has the potential to be used in the prevention of age-related obesity.